Fourier Analyse des Abflussregimes im westlichen Zentralafrika - Herrmann, Reimer (ERDKUNDE, 1970)
Seasonal changes in the mean monthly runoff of 18 river basins in western Central Africa were subjected to a Fourier analysis. The amplitudes and phase angles of the first three harmonic components were mapped, as well as the total variance, the variance of the first two harmonic components and the ratio between the variance of the first harmonic component and that of the second. Using these maps it is possible to distinguish between a region covering the southern coastal heights of Cameroon which exhibits double seasonality in its runoff regime and another region in the Cameroon Mountains which has a distinct annual tendency. Around Lake Chad a region with an annual tendency but low total variances has developed. The transitional regions are easily determined. The temporal and areal distribution of the runoff extremes can be explained by the seasonal shifting of the equatorial trough.